PUBLIC-PRIVATE PARTNERSHIP IN THE CONDITIONS OF DECENTRALIZATION: NEW OPPORTUNITIES FOR TERRITORIAL COMMUNITIES IN UKRAINE - Teslya, Andriy (Public Management and Policy, 2025)
The article examines the impact of the decentralization reform on the development of public-private partnership and new opportunities that are opening for territorial communities. It has been established that the transfer of powers and resources to the local level has given communities the status of full-fledged public actors with their own financial resources. Modern research and regulatory changes are analyzed, in particular the adoption of the new Law of Ukraine “On Public-Private Partnership” of 2025, which has simplified the procedures for attracting private capital and expanded the range of public partners. It is found that decentralization has expanded the institutional framework of public-private partnership, allowing communities to initiate projects in cooperation with business for the development of local infrastructure and services. The mechanisms of public participation in the implementation of public-private partnership at the local level and the need to ensure a balance of interests between government and business are considered. The experience of the first implemented agreements has demonstrated the benefits of public-private partnership for communities (modernization of roads, social infrastructure facilities, etc.) conditional on the proper allocation of risks and benefits. Attention is also focused on risks that hinder the development of constructive interaction between local government and business, imperfect legislation and the lack of public audit can lead to corrupt practices or the loss of municipal property. The study concludes that, in the context of increasing the financial independence of communities and participation in national reconstruction projects, PPP is an important tool for the innovative development of territories, but it requires transparent procedures, public participation, and strict compliance with legislation to ensure a long-term, mutually beneficial outcome.